Aronia melanocarpa polysaccharide ameliorates liver fibrosis through TGF-β1-mediated the activation of PI3K/AKT pathway and modulating gut microbiota - Yingchun Zhao; Xinglong Liu; Chuanbo Ding; Yinan Zheng; Hongyan Zhu; Zhiqiang Cheng; Chunli Zhao; Wencong Liu (Elsevier, 2022)
The purpose of this experiment was to investigate the anti-hepatic fibrosis effect of Aronia melanocarpa polysaccharide (AMP) on TAA-induced liver fibrosis mice and its mechanism, as well as the changes in intestinal flora in vivo. This was established with a dose of 200 mg/kg TAA (i.p) once every three days, lasting for eight weeks. Colchicine with 0.4 mg/kg, and AMP (200 and 400 mg/kg) were given by intragastric administration (i.g) after 28 days of intraperitoneal injection of TAA. AMP treatment significantly inhibited the activities of liver injury markers ALT and AST in serum. Histopathological staining demonstrated that AMP significantly reversed TAA-induced hepatocyte necrosis and collagen deposition. In addition, AMP treatment block TGF- β1/Smads pathway inhibited the production of ECM and alleviates liver fibrosis. Furthermore, AMP treatment enhanced the phosphorylation of PI3K/AKT and decreased the expression of its downstream apoptosis-related proteins in liver, thus effectively alleviating TAA-induced liver fibrosis. In addition, 16S rDNA gene sequencing analysis showed that AMP treatment helped restore the imbalanced ecosystem of gut microbes, increased the proportion of Bacteroidetes and Proteobacteria, and increased species richness. Above findings clearly show that AMP is an effective method for treating liver fibrosis, possibly by improving the gut microbiota.